Occupations and Skills Radar : Background Information on Development and Objectives - Schnepf, Timo [Verfasser] (Bundesinstitut für Berufsbildung, 2025)
"This report contains background information on the development and objectives of the Occupations and Skills Radar. Five application examples demonstrate the added value of the new data portal for the target group of experts, politicians, researchers, and interested members of the public. The report then shows how the data portal works. It explains how different data is integrated, how the best data for the queries is automatically selected and displayed, and how intuitive user flow and experience are ensured. The report concludes with a market overview and the unique selling points of the portal in a national and international comparison." (BIBB-Autorenreferat)
Keywords: S 6 Berufsbereiche; G 1.1.4 Statistiken zu speziellen Problemlagen & Bereichen; S 1 Stufen der Berufsbildung; 370; Berufsbildungsforschung; Berufsbildung; Beruf; Open Science; Massendaten; Berufsbildungsstatistik; Berufsstatistik; Datawarehouse; Datenbank